Metabolically versatile large-genome prokaryotes - Guieysse, Benoit (2013)
Although versatile microorganisms are critical in industrial applications where the ability to cope with change and carry out complex tasks is needed, very little is in fact known about the evolutionary and ecological meanings of versatility in prokaryotes. Testing the hypothesis that a large genome size is a prerequisite for versatility in prokaryotes, we found that putatively versatile prokaryotes are phylogenetically and ecologically diverse and indeed include many well known and commercially relevant versatile microorganisms. Despite individual differences in metabolic abilities, a common trait of large-genome prokaryotes appears that they have gained their large genomes as an evolutionary response to nutrient-scarce and/or variable environments. This insight seriously questions the ability of traditional microbiology methods to isolate versatile prokaryotes and casts doubt on the ecological relevance of knowledge based on the study of specialists.